Effects of Waterlogging On Maize Seedling Growth during Seed Germination. Issue 1 (November 2020) - Xiong, Rui; Sang, Liran; Liu, Rui; Cheng, Ru; Li, Peishan; Huang, Liangjun; Cao, Gaoyi
Abstract: In order to understand the resistance of maize seed germination characteristics, to varying degrees of early germination of maize seeds flooding stress, explore the seed germination of maize seedling vigor and growth period of flooding stress, help to understand inverse resistant mechanism of corn seed germination period, to help agricultural production results show that the seeds of waterflooded development, continue to develop at a young age, compared with control, corn seedling variety of enzyme activity and soluble sugar and soluble protein in different degree of change Compared with the control group, the chlorophyll content of Lu yu 36 maize seedlings decreased, while the chlorophyll content of Zheng Dang 958 showed a trend of first decreasing and then increasing. Peroxidase (POD), malondialdehyde (MDA) and soluble sugar all showed an increasing trend. These results provided a basis for better understanding of the waterlogging stress tolerance of maize seeds during germination.